Plasmid expression vector encoding sFLT-1 receptor (psFLT-1) inhibits angiogenesis and L1 tumour growth - Małecki, Maciej; Gromek, Katarzyna; Przybyszewska, Małgorzata; Janik, Przemysław (Contemporary Oncology/Współczesna Onkologia, 2006)
Antiangiogenic gene therapy is based on genes encoding protein factors that suppress a process of new vessels formation – angiogenesis. It is common knowledge that angiogenesis is a crucial point of the tumour growth and metastasis formation. Therefore, many new anticancer strategies and drugs are focused on the inhibition of angiogenesis. psFLT-1 is a nonviral, plasmid expression vector encoding soluble form of vascular endothelial growth factor receptor VEGFR1 (sFLT-1). sFLT-1 gene encodes only extracellular domain of the VEGFR1 and specifically blocks proangiogenic activity of VEGF. The studies were performed on laboratory animals subcutaneously or intraperitoneally injected with mouse L1 fibrosarcoma cells or their psFLT-1 transfectants. The new vessels formation, and tumour growth, and survival time were evaluated on tested animals. The obtained outcomes revealed that psFLT-1 expression vector efficiently inhibits pVEGF induced angiogenesis as was measured by two in vivo angiogenesis tests. It was also shown the inhibitory psFLT-1 effect on L1 tumour growth and survival time of the L1 intraperitoneally injected animals. The prolonged survival time of L1/psFLT-1 animals was clearly observed. Finally, the clinical application of psFLT-1 gene construct was taken under consideration. At present, psFLT-1 based antiangiogenic clinical trial is in progress in the Centre of Oncology in Warsaw.